2008
DOI: 10.1353/cpr.0.0046
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Research in Native Communities

Abstract: People are living longer because of advances made through biomedical research. The challenge in genetic research on indigenous peoples is that it raises a complex range of legal, ethical, social, spiritual, and political issues. The current research paradigm is one of paternalism and biocolonialism. Such was the case of the Havasupai, who believed their blood samples were to be solely used for their collective benefit and well-being, and Native Hawaiians, who are opposed to genetically modified taro. Pertinent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 7 publications
0
37
0
Order By: Relevance
“…Communities may lack linguistic or conceptual equivalents for technical terms such as “penetrance;” and certain words, such as “mutation,” carry negative connotations in everyday language [Condit et al, 2004]. In some cases, genetic research may simply not be a priority for the community [James and Starks, 2011] or may raise concerns over misuse or misappropriation [Foster et al, 1999; Santos, 2008]. …”
Section: Introductionmentioning
confidence: 99%
“…Communities may lack linguistic or conceptual equivalents for technical terms such as “penetrance;” and certain words, such as “mutation,” carry negative connotations in everyday language [Condit et al, 2004]. In some cases, genetic research may simply not be a priority for the community [James and Starks, 2011] or may raise concerns over misuse or misappropriation [Foster et al, 1999; Santos, 2008]. …”
Section: Introductionmentioning
confidence: 99%
“…The loss of land and cultural practices, drastic changes in dietary patterns, and the lack of access to educational and socioeconomic opportunities that are connected with NHPI cultural values 1316 continues to contribute to health disparities that are among the worst in the nation. 1720 Unethical research in these communities includes the well-documented experimentation done without consent to Hansen’s disease patients in Kalaupapa, Hawai‘i 21 and nuclear bomb testing on an inhabited Pacific Ocean atoll. 22 These studies, as well as other less known research, have led to exploitation and harmful stereotyping, compounding suspicion among community members toward the research enterprise.…”
mentioning
confidence: 99%
“…The research on schizophrenia, inbreeding, and population migration theories did not benefit their nation in any way and instead subjected them to stigma and emotional and mental anguish (Drabiak-Syed, 2010). For example, the research on migration suggested that the Havasupai migrated from a geographic location inconsistent with their worldview (Santos, 2008). Furthermore, the findings from the diabetes testing hypothesized that the high prevalence of diabetes was a result of a nutrient deficiency in pregnancy (Rubin, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the findings from the diabetes testing hypothesized that the high prevalence of diabetes was a result of a nutrient deficiency in pregnancy (Rubin, 2004). No intervention efforts were made as a result of these findings, indicating that the best interest of the Havasupai Nation was not considered (Santos, 2008). People with diabetes from the Havasupai Nation now have to be treated with dialysis because they did not seek medical treatment in time due to the fear and mistrust that occurred as a result of this project (Boomersbach, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation